Penerapan unsur layak berita pada subkanal daerah rri.co.id Jaringan Jakarta - Gunawan, Cecep (Program Studi Penerbitan, Politeknik Negeri Jakarta, 2024)
Mass media was born as a tool or channel used to disseminate information to a wide audience, usually including a large number of individuals or the general public. Mass media is media intended for the masses. In journalism, mass media broadcast news or information, also known as the press. In presenting news, aspects of freedom and accuracy are very important to pay attention to. News must be independent, not a form of advertising, and delivered through the media the masses as active intermediaries and disseminating factual and actual information to the public. In an era of increasingly sophisticated technology, the dissemination of information has become faster and easier to access by anyone and anywhere via gadgets. News must first be careful and precise or deep journalistic language must accurate. Apart from being accurate and precise, news must also be complete, fair and balanced. Newsworthy elements include: Accurate: Reporters must be thorough in spelling, numbers, dates, and ages, and double-check information to ensure details and general impression are correct; Complete, Fair and Balanced: Accuracy of facts must be accompanied by a fair and balanced presentation, reporting what actually happened; Objective: News must be written objectively, reflecting reality without partiality or prejudice; Concise and Clear: News must be easy to understand, straight to the point, and well structured; Warm: News should be new and relevant, emphasizing elements of time and current events.